2016
DOI: 10.1080/13102818.2016.1154802
|View full text |Cite
|
Sign up to set email alerts
|

Visibility of the mandibular canal on cross-sectional CBCT images at impacted mandibular third molar sites

Abstract: The aim of the present study was to assess visibility of the mandibular canal (MC) on cross-sectional cone beam CT (CBCT) images at impacted mandibular third molar (IMTM) sites. CBCT images for 150 IMTMs were selected for the study. The type of tooth impaction (horizontal, vertical, mesial and distal) and location of the MC (inferior in contact and superimposed) were evaluated on pseudopanoramic images. Cross-sectional images were generated and two observers evaluated the location of the MC (buccal, lingual, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Alkhader & Jarab [ 19 ] assessed the visibility of IAC (on cross-section CBCT) at the impacted mandibular third molar sites where they found that most sites showed “very good to excellent” visibility levels.…”
Section: Discussionmentioning
confidence: 99%
“…Alkhader & Jarab [ 19 ] assessed the visibility of IAC (on cross-section CBCT) at the impacted mandibular third molar sites where they found that most sites showed “very good to excellent” visibility levels.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature has extensively studied the relationship between impacted mandibular third molars (ITMs) and the mandibular canal, highlighting the importance of accurate preoperative assessments to prevent nerve injuries. However, there remains a need for further investigation specifically focusing on IMTMs to provide a comprehensive understanding of their distinct characteristics and spatial positioning in relation to the mandibular canal [ 16 18 ]. To expand the sample size of this research topic, the current paper observed the imaging data of 101 cases of IMTMs in close contact with the mandibular canal by CBCT and dynamically analysed the location of the IAN across the IMTM region to provide an additional clinical reference for the extraction of IMTMs.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) imaging such as cone-beam computed tomography (CBCT) has an excellent capacity to visualise the anatomical relationship between the tooth and nerve [7]. Understandably therefore, dentists and oral surgeons have increasingly become interested in the ability of CBCT to detail in 3D the anatomical relationship of the IDN to MTM in the hope of reducing iatrogenic injuries during surgery.…”
Section: Introductionmentioning
confidence: 99%